Empirical evidences on production performance and economics of pulses cultivation in Bihar - KUMAR, ABHAY; SINGH, R K P; CHOUDHARY, A K; SINGH, K M; KUMAR, UJJWAL; KUMAR, PANKAJ (The Indian Journal of Agricultural Sciences, 2021)
Pulse crops are important for providing healthy diets to human being and protein-rich feed and fodder to animals. Bihar is one of the major states for pulses production in the country. The study was carried out at Patna during 2017-19 and based on secondary data for the last 37 years period obtained from published documents and reports of Government of Bihar. Despite the institutional support to increase pulses production, area and production have been declining during the period under study due to lower productivity compared to the competing cereal crops in Bihar. It is paradox that per hectare net income and other measures of income are higher in pulses cultivation than wheat production in winter season but the weaker section of farming community prefer to cultivate wheat to ensure their food security. However, there is a dearth of appropriate technology for pulses production which needs urgent attention by scientific community and policy makers to reverse the cropping pattern in favour of pulses production.